2021
DOI: 10.1177/15330338211041212
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Salvage Radiotherapy for Locoregional Clinical Recurrence After Radical Prostatectomy

Abstract: Objectives: To assess the clinical outcomes of prostate cancer patients treated with salvage radiotherapy (SRT) for locoregional clinical recurrence (CR) after radical prostatectomy (RP). Methods: Records of 60 patients with macroscopic locoregional recurrence after prostatectomy and referrals for SRT were retrospectively investigated in the multi-institutional database. The median radiation dose was 70.2 Gy. Biochemical failure was defined as the prostate-specific antigen (PSA) ≥ nadir + 2 or initiation of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…This is in line with the published data on salvage radiotherapy for macroscopic local prostate cancer recurrence, as Bruni et al, Zilli et al, and Zaine et al did not observe a benefit in biochemical control from higher doses [12][13][14]. For dose-escalation, most published studies utilized a sequential boost or a SIB at two dose levels [10,[12][13][14][15]. The radiotherapy concept for macroscopic local recurrence at our institution included a SIB at up to three dose levels: PTV Boost1 encompassed the prostate bed and spared the rectum, while the highest dose, PTV Boost2 , encompassed the macroscopic local recurrence without an additional margin.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…This is in line with the published data on salvage radiotherapy for macroscopic local prostate cancer recurrence, as Bruni et al, Zilli et al, and Zaine et al did not observe a benefit in biochemical control from higher doses [12][13][14]. For dose-escalation, most published studies utilized a sequential boost or a SIB at two dose levels [10,[12][13][14][15]. The radiotherapy concept for macroscopic local recurrence at our institution included a SIB at up to three dose levels: PTV Boost1 encompassed the prostate bed and spared the rectum, while the highest dose, PTV Boost2 , encompassed the macroscopic local recurrence without an additional margin.…”
Section: Discussionsupporting
confidence: 82%
“…We escalated the radiation dose to the local recurrence up to a median total dose of 69.3 Gy, which is comparable to the studies of Zaine et al and Lee et al [13,15]. In primary prostate cancer, the FLAME trial demonstrated better biochemical control by doseescalating the GTV up to 95 Gy [31].…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations